2015
DOI: 10.1038/srep12085
|View full text |Cite
|
Sign up to set email alerts
|

Small-angle X-ray scattering method to characterize molecular interactions: Proof of concept

Abstract: Characterizing biomolecular interactions is crucial to the understanding of biological processes. Existing characterization methods have low spatial resolution, poor specificity, and some lack the capability for deep tissue imaging. We describe a novel technique that relies on small-angle X-ray scattering signatures from high-contrast molecular probes that correlate with the presence of biomolecular interactions. We describe a proof-of-concept study that uses a model system consisting of mixtures of monomer so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 53 publications
1
29
0
Order By: Relevance
“…No form of intermolecular interaction, be it attractive, repulsive, hydrophobic etc can ensue outside the region of mutual perturbative influence. The quantification of interactions (which is a function of vectorial motion) between biomolecules is essential for understanding the molecular basis of biological processes (rate of digestion, passive transport etc) [45]. Here there is need to define interaction in the light of Kirkwood-Buff solution theory [46].…”
Section: Usefulness Of Translational Velocitymentioning
confidence: 99%
“…No form of intermolecular interaction, be it attractive, repulsive, hydrophobic etc can ensue outside the region of mutual perturbative influence. The quantification of interactions (which is a function of vectorial motion) between biomolecules is essential for understanding the molecular basis of biological processes (rate of digestion, passive transport etc) [45]. Here there is need to define interaction in the light of Kirkwood-Buff solution theory [46].…”
Section: Usefulness Of Translational Velocitymentioning
confidence: 99%
“…There are an increasing number of imaging applications for small-angle X-ray scattering (SAXS) using scanning (Gourrier et al, 2007) and tomographic methods (Schroer et al, 2006;Jensen et al, 2011). We have proposed a particular biomedical application that utilizes SAXS molecular imaging of probed protein-protein interactions (Allec et al, 2015). SAXS imaging is a promising alternative tool for in vivo molecular imaging because the coherent scattering provides nanostructural information about a sample without the need for destructive sample preparation techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Well defined SAXS signatures from high-contrast molecular probes, such as gold nanoparticles (GNPs), could be correlated with the presence of biomolecular interactions and provide a higher-specificity option that is able to image protein-protein interactions in vivo in deep tissue. It was demonstrated that GNP signals could be determined even within a complex background such as Escherichia coli lysate (Allec et al, 2015). However, concerns remain regarding the long measurement times and the excessive amount of energy deposited into live samples.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…solvent subtraction and contrast), and molecular modeling. Research involving the SAS method has accelerated in recent years, which includes the characterization of molecular interactions [1] and the development of software for comparing atomistic models with data from SAS [11].…”
mentioning
confidence: 99%